Effect of Oral Hygiene on Prevention Ventilator Associated Pneumonia (VAP) in The Intensive Room of The Hospital Granmed Lubuk Pakam in 2023 - Pitriani; Lismawati; Yohana Adelina Pasaribu (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Mechanical ventilation is used to save the condition of critical patients in the intensive care unit, but prolonged use causes an increased risk of infection and various complications. The usual potential complication is infection. The most common infection resulting from mechanical ventilation is Ventilator-Associated Pneumonia (VAP). VAP is a major cause of mortality, morbidity, and extends the duration of use of mechanical ventilation and prolongs hospitalization, thereby increasing treatment costs. The aim of this research is to see the effect of oral hygiene measures on preventing ventilator associated pneumonia (VAP) in the intensive care unit at Grandmed Lubuk Pakam Hospital in 2023. This type of research is quantitative research using a quasi-experimental research design with pretest-posttest. The research sample was 35 respondents. The research results showed that there was an influence of oral hygiene on the prevention of ventilator associated pneumonia (VAP) in the intensive care unit at Grandmed Lubuk Pakam Hospital in 2023 with a P value of 0.00 where the value of ? = 0.05 from these results if compared to the value of P < ? then Ha accepted. It is hoped that the hospital will be able to increase the comfort of patients with decreased consciousness who are on ventilators.